(untitled) (Південний архів (історичні науки), 2021)
The purpose of the work. The article is devoted to the fate of Volksdeutsche women after the end of the Second World War. The focus is on the history of women in southern Ukraine, a region of Ukraine where a large part of the German population is under occupation. The historiography of the problem covers works that cover the issue of gender history in the context of the topic: Larysa Belkovets, Lyudmila Burgart, Andriy Kotlyarchuk, Maya Lutai, Olena Styazhkina and others. The sources of the study were the NKVD investigative cases against women who accepted German citizenship, eyewitness accounts, and statistics. Results and scientific novelty of the study. The circumstances and reasons why women chose the status of Volksdeutsche have been clarified. In particular, the study found that this was not always a voluntary or conscious choice: women in difficult life situations chose a survival strategy that they thought could be successful. Volksdeutsche status did not guarantee a happy life, adequate nutrition or normal living conditions for the woman and her family. He was entitled to minimal assistance, but imposed many responsibilities on the Volksdeutsche, forcing them to accept Nazi crimes against civilians and send their children to Hitler’s or the German Girls’ Union, where they were raised in the spirit of Nazi ideology. German women seldom took an active part in collaborationism: they seldom worked as translators, teachers for Volksdeutsche and Ukrainian schools that did not last long in the occupied territories. In the south of Ukraine, the Volksdeutsche also included ethnic Swedes – residents of the Swedish colony Staroshvedske. For the Germans of southern Ukraine in the status of Volksdeutsche, the war ended first with the forced evacuation to Germany by the Germans, and then by the forced repatriation of Soviet troops home. As a result, Volksdeutsche women were tried on charges of treason and aiding the Nazis. Women made up the majority of special settlers in Siberia, the Urals, and Kazakhstan. However, many Germans managed to avoid repatriation and remain in European countries forever without Soviet influence.